PROSPEK USAHA INOVASI SPEAKER DAN PAJANGAN UNIK UPAYA PEMANFAATAN LIMBAH GULUNGAN KERTAS - Saputri Rizki Ramadhanti; Joti Dina Kartikasari; Alfian Muttoqim Muttoqim; Umi Farida Farida; Amanda Oktaviani Amanda (Politeknik Negeri Semarang, 2019)
The amount of paper waste, especially paper waste of yarn rolls in the socks manufactured factory and the convection industry that has not been used to get high economic value is an opportunity to open a new business, especially in the electronic and art craft product. SEPIK PANIK (Speaker of Music and Unique Display of Waste Paper Rolls) is an innovation from processing paper waste to be a unique speaker. The purposes of this program are: 1) Utilizing paper waste to get high selling value. 2) Creating handmade products from paper waste into speakers as well as unique creative display. 3) To accommodate the desire of college students who have entrepreneurial spirit and artistic creations to open new business opportunities. The method of make this SEPIK PANIK product includes 1) Making paper tube of speaker and 2) Making a Unique Display. The Sales of this product have been carried out during May to August 2019, products that have been sold are 34 units, obtained a profit of Rp. 1.170,000. Sales and promotion methods are carried out both online through social media and offline, namely direct selling and consignment. Based on these results, this business is very profitable and can benefit the surrounding environment.